(untitled) (Research, Society and Development, 2021)
The environment and health relation is a theme that is being highlighted in debates and scientific events aiming at quality of life in our society. The necessary link between health and environmental aspects rose when the WHO (1946) defined health as a state of complete physical, mental and social well-being and not just as the absence of disease or illness. In Brazilian education, environment and health themes were initially encouraged through the National Curriculum Parameters, together with other issues through transversal themes, and the idea of promoting emerging issues development in all basic education areas of knowledge. Due initial and continuing training of teachers deficiency regarding the proposed themes, their approach often ends up being limited to specific dates and in a superficial and decontextualized way. Aiming at correct and adequate dissemination of these important themes that can improve the quality of life of society, the present study sought to diagnose how the environment and health themes are approached by teachers from four municipal middle schools of Alegrete / RS. After analyzing the data, it can be inferred that results reflect a scenario in which the environment and health themes approach occurs, however, in a disconnected and decontextualized way most of the time and with the environment theme being more valued than the health theme, disfavoring its link with the environment and consequently the relationship with the students’ quality of life.